Etika Bimbingan dan Konseling dalam Pendekatan Filsafat Ilmu - Alfaiz Faiz; Ari Dharmayanti; Nofrita Nofrita (Universitas Mathla'ul Anwar Banten, 2018)
ETHICS OF GUIDANCE AND COUNSELING IN PHILOSOPHY OF SCIENCE APPROACH. In philosophy view, ethic was a valueable and evaluation about a good and bad things in the human self. Ethic is also call moral philosophy as a apart of axiology in science philosophy. In every science has an axiology that purpose of utilization for prosperity of a human life. Guidance and counseling is a science full of values, that because of it’s a multidicipliner science. This based of four field guidance which of personal, learning, social and career. This field has make a counselor must understand and proficiency with sociology, antrophology, psychology, and eduation science. That will lead a counseling as multidicipliner science has a full of values to covering the process of counseling practice. However the axiology of counseling make little complex to discuss in philosophy foundation, also in psychology, sociology, antrophology and education. In this article will describe and discuss an ethics in counseling as a multidicipliner science in the view point of philosophy, psychology, and education. Also an ethics in counseling profession as applicative science.